Existing and Potential Applications of Elastography for Measuring the Viscoelasticity of Biological Tissues In Vivo - Zhang, Kaiwen; Zhu, Min; Thomas, Evan; Hopyan, Sevan; Sun, Yu (Frontiers in Physics, 2021)
Mechanical tissue properties contribute to tissue shape change during development. Emerging evidence suggests that gradients of viscoelasticity correspond to cell movement and to gene expression patterns. To accurately define mechanisms of morphogenesis, a combination of precise empirical measurements and theoretical approaches are required. Here, we review elastography as a method to characterise viscoelastic properties of tissue in vivo. We discuss its current clinical applications in mature tissues and its potential for characterising embryonic tissues.